Pengaruh Pre-Treated Dentin Menggunakan Flavonoid dan Agen Remineralisasi yang Berbeda - Putri, Shahnaz Dwi Permata; Eriwati, Yosi Kusuma (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2023)
The bond resistance of caries-affected dentin is questionable compared to healthy dentin. This is caused by partial demineralization resulting in loss of integrity of the hybrid layer by collagenolytic enzymes, namely matrix metalloproteinases (MMPs). This enzyme is responsible for the degradation of the collagen matrix in the hybrid layer. Based on this, new strategies have been used in which the use of flavonoids as exogenous crosslinking agents has been suggested as a method to inhibit MMP activity, such as Quercetin, Hesperidin, Rutin and Naringin. In addition, partially demineralized dentine is remineralized to improve its mechanical or bonding properties using a remineralizing agent. Purpose: This study aims to evaluate the effect of pre-treatment of dentin using various flavonoids and remineralizing agents. The effects of pre-treated dentin will be discussed in this review both with flavonoids, remineralizing agents and their use together. Conclusion: The effect of pre-treated dentin using various flavonoids and remineralizing agents can increase the strength of the resin-dentin bond.